A new method developed to characterize the 3D microstructure of frozen apple using X-ray micro-CT. (November 2017) - Vicent, Victor; Verboven, Pieter; Ndoye, Fatou-Toutie; Alvarez, Graciela; Nicolaï, Bart
Abstract: Non-destructive imaging techniques have become indispensable to improve insights into the microstructural changes occurring in fruit tissue during freezing. Here, apple cortex tissue samples were frozen using different freezing rates: (i) slow freezing (2.0 °C per min.), (ii) intermediate freezing (12.6 °C per min.) and fast freezing (18.5 °C per min.). Temperature-controlled X-ray micro-CT was optimized and then applied to visualize and quantify the 3D microstructure and ice crystal distribution at a pixel resolution of 3.8 μm. Ice crystal size distributions with mean equivalent diameters of about 41 ± 3.5 μm, 55 ± 7.4 μm and 71 ± 9.6 μm were obtained for the fast, intermediate and slow freezing rates, respectively. A new imaging methodology was developed and validated to allow segmentation of the ice crystals in frozen apple tissue using the X-ray attenuation coefficients of the reference model samples, i.e. frozen pure water and concentrated apple juice. Highlights: First study of the full 3D microstructural changes of apple tissue during freezing. X-ray μCT was applied to study the 3D microstructural changes during freezing. Different freezing methods show significant difference in the 3D microstructure of the frozen apple tissue. A new method to characterize the ice crystals and the 3D microstructure in plant-based products.